Scenes of Berlin: Fascism and Anti-Fascism in Toronto during the Summer of 1938 - Wentzell, Tyler (Canadian Jewish Studies / Études juives canadiennes, 2023)
Four significant fascist rallies took place in Toronto in the summer of 1938: John Ross Taylor’s Canadian Union of Fascists, Joseph Farr’s Nationalist Party, and then two rallies to establish the National Unity Party—a national fascist party fusing Farr’s group, Adrien Arcand’s Quebec-based Parti National Social Chrétien, and other fascist groups from across the country. This article examines these fascist groups and their rallies, as well as the anti-fascist resistance. It focuses on the protests organized by the Provisional Anti-Fascist Committee consisting of the League for a Revolutionary Workers’ Party, the Toronto Libertarian Group, and working-class Jewish organizations. In examining these actors and events, the article seeks to demonstrate the complex dynamic of coordination and competition amongst fascist and anti-fascist actors.